2016
DOI: 10.1136/bmjopen-2016-013401
|View full text |Cite
|
Sign up to set email alerts
|

Randomised feasibility study of a novel experience-based internet intervention to support self-management in chronic asthma

Abstract: ObjectiveTo determine the feasibility of a randomised controlled trial (RCT) assessing the effects of an experience-based website as a resource for the self-management of chronic asthma.Design and settingFeasibility, single-blind RCT in 2 regions of England. Randomisation used computer-generated random number sequence in a 1:1 ratio, after baseline data collection, to website access for 2 weeks.ParticipantsAdults (age ≥18 years), with clinically diagnosed asthma as coded in their primary care electronic record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…The number of studies on ehealth interventions has grown rapidly in the last few years. Studies among patient or general populations have shown that e-health interventions enhance health and wellbeing, improve lifestyle and increase self-management for a broad range of diseases or risk factors (16)(17)(18)(19)(20)(21). In occupational health, however, articles on e-health interventions are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies on ehealth interventions has grown rapidly in the last few years. Studies among patient or general populations have shown that e-health interventions enhance health and wellbeing, improve lifestyle and increase self-management for a broad range of diseases or risk factors (16)(17)(18)(19)(20)(21). In occupational health, however, articles on e-health interventions are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Responsiveness has been demonstrated in a population of ambulatory patients with osteoarthritis in Australia [42,43]. Items are rated on a nine-point scale and averaged for each domain, higher scores referring, for example, to a more active role.…”
Section: Questionnairesmentioning
confidence: 99%
“…(12)(13)(14) When faced with new health concerns or treatments, patients search not only for fact-based information but also seek other patient experiences (PEx). (15) There is limited but increasing research looking at the value of PEx. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) The design and quality of these studies including PEx as an intervention varies.…”
mentioning
confidence: 99%
“…(15) There is limited but increasing research looking at the value of PEx. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) The design and quality of these studies including PEx as an intervention varies. (19,25) Also, there is no agreed-upon operationalisation of PEx, which are also called narratives, exemplars, anecdotes, testimonials or case histories.…”
mentioning
confidence: 99%